Hubungan Antara Dukungan Sosial Orang Tua Dengan Kemandirian Anak Usia 4-5 Tahun di Nagari Sikucur Kabupaten Padang Pariaman - Wahyuni, Sri; Sunarti, Vevi (Universitas Negeri Padang, 2025)
This research is motivated by the low level of independence of 4-5 year-old children in Sikucur Village, Padang Pariaman Regency. This is thought to be caused by parental social support. The purpose of this study was to describe parental social support, the level of independence of 4-5 year-old children, and the relationship between parental social support and the independence of 4-5 year-old children in Sikucur Village, Padang Pariaman Regency. This research was correlational and used a quantitative approach. The study population was 40 parents of 4-5 year-old children, 70% of whom were selected using area random sampling. A questionnaire was used as the data collection technique. Data analysis used percentage and ranking formulas. The results showed that parental social support was low and the independence of 4-5 year-old children in Sikucur Village, Padang Pariaman Regency was still low. There was a significant relationship between parental social support and the independence of 4-5 year-old children in Sikucur Village, Padang Pariaman Regency. Parents are advised to pay more attention to their children's development, especially regarding independence. Future researchers are advised to examine other variables related to parental social support and independence in early childhood at a higher age.